Different inoculating, forms of inoculation and their effects on the agronomic characteristics of soy culture (Research, Society and Development, 2020)
Biological nitrogen fixation replaces, at least in part, nitrogen fertilization and reduces production costs. Normally seeds are inoculated with bacteria, but there is technology to apply inoculants also in the sowing furrow, which allows increasing the possibilities of inoculation. In this work, it was evaluated the inoculation of different bacteria, applied alone or jointly, via furrow or seed on agronomic characteristics and soybean nitrogen extraction, in an area with a history of crop production. The experiment was a randomized block design in a 2x3 + 2 factorial scheme: seed or furrow application; Bradyrhizobium only, Azospirillum brasilense only and co-inoculation Bradyrhizobium + Azospirillum brasilense; two more witnesses (no inoculation). With seed inoculation, the lowest insertion heights of the first pod were verified with Bradyrhizobium and with co-inoculation, in furrow the control showed the highest result. Co-inoculation in seed presented the largest amount of pods per plant, when the application was in furrow the inoculation with Bradyrhizobium and co-inoculation stood out. The largest amount of grains per pod was obtained by inoculation with Bradyrhizobium and co-inoculation in seed, no differences were found in furrow. The largest mass of one thousand grains and productivity were obtained by inoculation with Bradyrhizobium and co-inoculation, regardless of the application form. Bradyrhizobium treatment and co-inoculation extracted more nitrogen in seed application, for the furrow the best result was with co-inoculation.